Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1074/jbc.m108369200
|View full text |Cite
|
Sign up to set email alerts
|

The Seven Amino Acids of Human RAMP2 (86) and RAMP3 (59) Are Critical for Agonist Binding to Human Adrenomedullin Receptors

Abstract: When co-expressed with a receptor activity-modifying protein (RAMP) accessory protein, calcitonin receptorlike receptor (CRLR) can function as a calcitonin generelated peptide receptor (CRLR-RAMP1) or an adrenomedullin (AM) receptor (CRLR-RAMP2/3). Here we report on the structural domain(s) involved in selective AM binding that were examined using various RAMP chimeras and deletion mutants. Co-expression of chimeric RAMPs and CRLR in HEK293 cells revealed that residues 77-101, situated in the extracellular N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 22 publications
4
56
1
1
Order By: Relevance
“…Neither 10 nM h␣CGRP nor hAM elicited significant increases in cAMP in nontransfected HEK-293 cells or cells transfected with HA-hRAMP1 or hCRLR alone. On the other hand, the coexpression of hCRLR with HA-hRAMP1 enabled CGRP and AM to each elicit significant increases in cAMP, which is consistent with previous reports that CGRP and AM bind to the CRLR/RAMP1 heterodimer with similar affinities (8,9,12,24,25). Similar CGRPand AM-evoked increases in cAMP levels were seen when hCRLR was co-expressed with D74-76, D105-107, or D109-112.…”
Section: Construction and Characterization Of Hramp1 Deletion Mutants-supporting
confidence: 78%
See 4 more Smart Citations
“…Neither 10 nM h␣CGRP nor hAM elicited significant increases in cAMP in nontransfected HEK-293 cells or cells transfected with HA-hRAMP1 or hCRLR alone. On the other hand, the coexpression of hCRLR with HA-hRAMP1 enabled CGRP and AM to each elicit significant increases in cAMP, which is consistent with previous reports that CGRP and AM bind to the CRLR/RAMP1 heterodimer with similar affinities (8,9,12,24,25). Similar CGRPand AM-evoked increases in cAMP levels were seen when hCRLR was co-expressed with D74-76, D105-107, or D109-112.…”
Section: Construction and Characterization Of Hramp1 Deletion Mutants-supporting
confidence: 78%
“…We also found that the same seven-residue segment situated between Trp-Cys and Tyr was conserved in rat RAMP2 and rRAMP3 (amino acids 93-99 and 58 -64, respectively) was also involved in agonist binding specificity (13). However, these findings did not enable us to draw any conclusions as to which structural domain(s) of human RAMP1 confer agonist specificity despite the use of the eight RAMP chimeras (RAMP1/2 and RAMP2/1) (12). Therefore, we decided to construct a group of deletion mutants that would enable a more detailed analysis of the extracellular domain of hRAMP1.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations